(untitled) (Nusantara Medical Science Journal, 2019)
Background: Stevens-Johnson Syndrome (SJS) is a rare but potentially life- threatening form of Severe Cutaneous Adverse Reaction (SCAR). SJS is mostly caused by drugs and is associated with high morbidity and mortality. Moreover, no standard treatment has been established for SJS. The aim of this study is to present epidemiological features, etiologies, clinical outcomes, medical histories, and treatments of SJS patients at the Inpatient Units Kemuning I and II Dr. Soetomo General Hospital between 2011 until 2015. Methods: This retrospective study used secondary data collected from medical records. All patients in the Inpatient Units Kemuning I and II of Dr. Soetomo General Hospital from the year 2011 until 2015 who was diagnosed SJS were included in this study. Result: There were 29 medical records consisting of 23 females and 6 males with the diagnosis of SJS found in 2011-2015. Most patients were aged 25-44 years old, with no family history of SJS. A majority first presented with a clinical history of fever. The main cause of SJS in this cohort was amoxicillin. Mucosal areas that were involved the most was the eye and mouth. Systemic treatments for patients were corticosteroid. The average duration of treatment was 15,88 days. None of the patients died. Conclusion: SJS was more common in females compared to males. The main systemic therapy in Inpatient Units Kemuning I dan II of Dr. Soetomo General Hospital was intravenous cortiosteroid and no patients died.